ETHIOPIAN SOCIAL CONFLICT IN THE NOVEL AẒ-ẒILL AL-ASWAD BY NAJIB AL-KAILANI BASED ON RALF DAHRENDORF'S PERSPECTIVE - Muhammad Hadiyan Ihkam; Muhammad Musthofa (Muaddib: Journal of Arabic Language and Literature, 2025)
This article aims to: (1) describe the form of social conflict between the empire and Ethiopian society  in the novel Aẓ-Ẓill Al-Aswad by Najib Al-Kailani based on Ralf Dahrendorf's perspective; (2) explain the causes of social conflict between the empire and Ethiopian society in the novel Aẓ-Ẓill Al-Aswad by Najib Al-Kailani based on Ralf Dahrendorf's perspective; and (3) find out the impact of social conflict between the empire and Ethiopian society in the novel Aẓ-Ẓill Al-Aswad by Najib Al-Kailani based on Ralf Dahrendorf's perspective. This type of research is descriptive qualitative research. The data source of this research is the novel Aẓ-Ẓill Al-Aswad by Najib Al-Kailani. The data collection techniques used are reading techniques and note-taking techniques. From the data findings, researchers test the credibility of the data. The data analysis technique consists of three stages, namely data reduction, data presentation, and conclusion drawing. The results of this study are: (1) the social conflict that occurred between the empire and the Ethiopian people based on Ralf Dahrendorf's perspective was arbitrary by the pseudo-group, cruel by the interest group, and rebellious by the conflict group; (2) the causes of social conflict between the empire and the Ethiopian people in the novel Aẓ-Ẓill Al-Aswad by Najib Al-Kailani based on Ralf Dahrendorf's perspective are pseudo-groups who want to maintain power, interest groups because they are arrogant, and conflict groups because they demand rights; and (3) the impact of social conflict between the empire and the Ethiopian people in the novel Aẓ-Ẓill Al-Aswad by Najib Al-Kailani based on Ralf Dahrendorf's perspective is rebellion and unity.